Frequency of Helicobacter Pylori Infection in Patients with Gastroduodenal Ulcer Perforation at Ayub Teaching Hospital Abbottabad - Najaf, Qaaneta Binte; Asad, Shawana; Junaid, Fazli; Salim, Farwa; Taj, Aimen; Rashid, Sabahat (Indus Journal of Bioscience Research, 2025)
Background: Gastro duodenal ulcer perforation is an emergency condition which cause leakage of gastric contents into abdominal cavity and can leads to sepsis if not treated early. Helicobacter pylori infection is considered important factor in ulcer diseases but its frequency in perforation cases in this region is not well known. Objective: To determine frequency of Helicobacter pylori infection in patients with gastro duodenal ulcer perforation. Study Design: Cross sectional study. Duration and Place of Study: This study was conducted from 27 February 2025 to 27 May 2025 in Department of Surgery Ayub Teaching Hospital Abbottabad. Methodology: Total 218 patients of both gender with age 18 to 70 years were included. Helicobacter pylori infection was assessed by available diagnostic methods. Data was analysed by statistical package for social sciences version 27. Stratification was done and Chi square test or Fisher exact test was applied, p value ≤0.05 was taken as significant. Results: Mean age was 48.93 ± 14.34 years. Male were 144 (66.1%) and female were 74 (33.9%). Helicobacter pylori infection was present in 152 (69.7%) patients while 66 (30.3%) were negative. No significant association was found with age (p=0.799), gender (p=0.170), body mass index (p=0.451), socioeconomic status (p=0.279), education (p=0.134), residence (p=0.064) and duration (p=0.702). Conclusion: Helicobacter pylori infection is common in patients with gastro duodenal ulcer perforation and may have important role in disease, but no significant association with demographic factors was seen.